1998
DOI: 10.1074/jbc.273.52.35102
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll a Formation in the Chlorophyll bReductase Reaction Requires Reduced Ferredoxin

Abstract: The reduction of chlorophyllide b and its analogue zinc pheophorbide b in etioplasts of barley (Hordeum vulgare L.) was investigated in detail. In intact etioplasts, the reduction proceeds to chlorophyllide a and zinc pheophorbide a or, if incubated together with phytyldiphosphate, to chlorophyll a and zinc pheophytin a, respectively. In lysed etioplasts supplied with NADPH, the reduction stops at the intermediate step of 7 1 -OHchlorophyll(ide) and Zn-7 1 -OH-pheophorbide or Zn-7 1 -OH-pheophytin. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 39 publications
6
58
0
Order By: Relevance
“…It encodes a chloroplast-localized protein that contains an iron-sulfur cluster and a FAD-binding pocket. Recombinant HCAR catalyzed reduction of C7-hydroxymethyl Chl a to Chl a in the presence of reduced ferredoxin, in agreement with its proposed biochemical properties (Scheumann et al 1998). Interestingly, HCAR has high sequence homology to cyanobacterial divinyl reductases, which catalyze reduction of the C8 vinyl moiety of divinyl-protochlorophyllide to an ethyl group during Chl biosynthesis.…”
Section: Chlorophyll Catabolic Enzymessupporting
confidence: 49%
See 1 more Smart Citation
“…It encodes a chloroplast-localized protein that contains an iron-sulfur cluster and a FAD-binding pocket. Recombinant HCAR catalyzed reduction of C7-hydroxymethyl Chl a to Chl a in the presence of reduced ferredoxin, in agreement with its proposed biochemical properties (Scheumann et al 1998). Interestingly, HCAR has high sequence homology to cyanobacterial divinyl reductases, which catalyze reduction of the C8 vinyl moiety of divinyl-protochlorophyllide to an ethyl group during Chl biosynthesis.…”
Section: Chlorophyll Catabolic Enzymessupporting
confidence: 49%
“…The two enzymes catalyzing these consecutive reactions, Chl b reductase and hydroxymethyl Chl a reductase (HCAR), have different biochemical properties; while the latter is a ferredoxin-dependent, stroma-localized enzyme, Chl b reductase localizes to the thylakoid membrane and requires NADPH as electron source (Ito et al 1996;Scheumann et al 1998Scheumann et al , 1999. Genes encoding both enzymes have recently been identified Meguro et al 2011).…”
Section: Chlorophyll Catabolic Enzymesmentioning
confidence: 99%
“…By analogy, this enzyme activity was found to also convert the nonesterified precursor of Chl b, Chlide b, as well as pyrochlorophyllide b and the magnesium-free pheophorbide b into the respective Chl a and 7-hydroxy compounds (23)(24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent paper, Scheumann et al (21) even generally questioned the existence of Pchlide b, but at the same time demonstrated that barley etioplasts rapidly convert exogenously added zinc protopheophorbide b (ZnPPb) to ZnPPa. This prompted us to conclude that Chl(ide) b reductase, presumably responsible for this conversion (22)(23)(24)(25)(26), could also metabolize the endogenously occurring Pchlide b to Pchlide a.…”
Section: For a Summary)mentioning
confidence: 99%
See 1 more Smart Citation